(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
This article explores cultural issues in literary translation from theoretical and practical perspectives. Literary translation is not merely a linguistic transfer but an intercultural process in which cultural meanings, values, and symbolic systems must be reconstructed in the target language. The study examines culture-specific items, realia, metaphors, pragmatic meaning, and sociolinguistic variation as major sources of translation difficulty. Drawing on functionalist, equivalence-based, and cultural approaches to translation, the article argues that successful literary translation requires intercultural competence and pragmatic awareness. The paper concludes with methodological recommendations for translator training and further academic research.